2014
DOI: 10.1021/ic500163c
|View full text |Cite
|
Sign up to set email alerts
|

A Tripodal Benzylene-Linked Trisamidophosphine Ligand Scaffold: Synthesis and Coordination Chemistry with Group(IV) Metals

Abstract: A new tripodal trisamidophosphine ligand (1) based on the trisbenzylphosphine backbone has been synthesized in three steps starting from NaPH2 and phthaloyl-protected 2-aminobenzyl bromide. At elevated temperatures, 1 reacts directly with M(NMe2)4 (M = Zr, Hf) to afford the dimethylamido complexes [PN3]M(NMe2) (M = Zr, Hf) (2), which are easily converted into the corresponding triflates [PN3]MOTf (M = Zr, Hf) (3) via reaction with triethylsilyl trifluoromethanesulfonate. The related titanium chloro complex [PN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 103 publications
0
9
0
Order By: Relevance
“…On the other hand, we have shown previously that related C 3 -linked trisamidophosphines (cf. systems D and E in Chart ) are well-suited to coordinate to group 4 metals in a tetradentate manner …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, we have shown previously that related C 3 -linked trisamidophosphines (cf. systems D and E in Chart ) are well-suited to coordinate to group 4 metals in a tetradentate manner …”
Section: Resultsmentioning
confidence: 99%
“…For the ethylene-linked trisamidophosphine ligand (phospha- tren , system C), no coordination compounds are known, although the Me 3 Si-substituted derivative of this ligand has been prepared by Schrock and co-workers (vide infra) . Very recently, we have obtained the o -tolylene- and the benzylene-linked ligands D and E (see Chart ) and demonstrated that these ligands coordinate in a tetradentate fashion ( endo -P configuration) . Taking these observations together, one might hypothesize that the configuration of the central phosphine is dependent on the length and flexibility of the N–C n –P linkage ( n = 1–3).…”
Section: Introductionmentioning
confidence: 98%
“…In agreement with the above mentioned expectation, the propylene-and benzylene-linked ligands, pr [NPN]H 2 and bn [NPN] H 2 , were readily synthesised following an adaption of our previously reported experimental procedure for the preparation of related triamidophosphine scaffolds (see Scheme S1 in the ESI †). 58,59 Both ligands were obtained in gram quantities and high purities, which allowed for their direct use to prepare the envisioned group 4 complexes shown in Chart 2.…”
Section: And Bn [Npn]hmentioning
confidence: 99%
“…Amidophosphine ligands combining hard nitrogen and soft phosphorus donor functionalities have been studied extensively because they combine the achetypal anchor functions for the two regimes of electron-rich and electron-poor metal atoms and thus act as versatile spectator ligands. In particular, PNP pincers, which constrain metals to certain geometries, have given rise to remarkable results in a variety of chemical transformations. The first monoanionic class of this ligands ( A , Figure ) with an aliphatic backbone was developed by Sacconi et al in the late 1960s . Fryzuk et al reported the synthesis of a similar PNP ligand with an SiMe 2 CH 2 backbone ( B ) and a number of early transition metal complexes which gave rise to remarkable results in the activation of small molecules. In 2003 Liang et al reported the synthesis of a o -phenylene-linked PNP pincer ligand C , which was modified by Ozerov et al in 2004.…”
Section: Introductionmentioning
confidence: 99%